If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9/10+x=-69/10
We move all terms to the left:
-9/10+x-(-69/10)=0
We get rid of parentheses
x-9/10+69/10=0
We multiply all the terms by the denominator
x*10-9+69=0
We add all the numbers together, and all the variables
x*10+60=0
Wy multiply elements
10x+60=0
We move all terms containing x to the left, all other terms to the right
10x=-60
x=-60/10
x=-6
| 105+7=4y | | -2(2n-22)+1=9 | | (7x-4)(6x-6)=38 | | -6=0.75(r+12) | | 4y=(15(7))+7 | | 395+3z=998 | | -14=4n+13+5n@-3 | | 1/b-5/8=3/4+3/8 | | 2(3x+4)+2=4x3x | | 6x-7x+7=3x-2x-5 | | 6x-21+20x+6=15x+40-3x-1 | | 862=20m+2 | | -4p=+9=-5 | | (7x+5)+(5x+19)=90 | | 9y-6=3y+18+6+6 | | 5x+5=10.5 | | 5(x-2)-7x=22 | | 5/84x-16=20 | | -14=4n+13+5n | | g+504=910 | | 2m-30=26 | | 21-x=17+11 | | w+322=508 | | 5j-26=14 | | n^2+45n=1000 | | m-73=24 | | (y+5)^2=0 | | a^2+25=256 | | y/12+25=29 | | 2/x+3=25 | | r-28=256 | | 5–3z–18=z–1+8z |